Double-layer asymmetric patch material for preventing air leakage after pulmonary operation as well as preparation method and application of double-layer asymmetric patch material

By combining hydrophilic polymer compound and electrospinning membrane, the two-layer asymmetric patch material prepared by combining hydrophilic polymer compounds and electrospinning membranes, the problems of poor bonding strength and durability of adhesive materials and the outer layer adhere to biological tissue in the prior art are solved, and the effect of efficient prevention of air leakage after lung surgery and avoiding postoperative adhesion is achieved.

CN119679992AActive Publication Date: 2025-03-25TIANJIN TUMOR HOSPITAL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411879214.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The adhesive material used in the prior art to prevent air leakage after lung surgery has poor adhesion strength and durability, and cannot adapt to the contraction and dilation of lung breathing. At the same time, the outer layer of the patch material is prone to adhere to other biological tissues, resulting in postoperative adhesion.

Method used

A 3D printed hydrogel patch is prepared by 3D printing using hydrophilic polymer compounds, acrylic acid, amine-coupling compounds, α-ketoglutaric acid and other raw materials, and combined with the electrospinning film through a specific bonding method to form a bilayer asymmetric patch material.

Benefits of technology

This double-layer asymmetric patch material has good adhesion properties and anti-adhesion ability, can effectively adhere to the wound surface without adhesion with other biological tissues, and has high tensile strength and fatigue resistance, adapts to lung respiratory movement, effectively prevents air leakage after lung surgery and avoids postoperative pleural adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119679992A_ABST
    Figure CN119679992A_ABST
Patent Text Reader

Abstract

The invention provides a double-layer asymmetric patch material for preventing air leakage after a lung operation as well as a preparation method and application of the double-layer asymmetric patch material, and relates to the field of biological adhesive materials. The preparation method of the double-layer asymmetric patch material comprises the following steps: mixing a hydrophilic high-molecular compound, acrylic acid, a compound of an amine coupling group, alpha-ketoglutaric acid, a cross-linking agent and water to obtain a hydrogel precursor solution, and performing 3D printing by using the hydrogel precursor solution to obtain a 3D printing hydrogel patch; mixing polyester with an organic solvent to obtain an electrostatic spinning solution, and performing electrostatic spinning to obtain a nanofiber membrane; a hydrogel precursor solution is used as an adhesive to bond a nanofiber membrane and a 3D printing hydrogel patch to obtain the double-layer asymmetric patch material, and the material has relatively high tensile strength and fatigue resistance, can conform to respiratory movement of the lung, is provided with an adhesive layer and an anti-adhesive layer, and can effectively solve the problem of postoperative pleural adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bioadhesive materials, and in particular to a double-layer asymmetric patch material for preventing air leakage after lung surgery, and a preparation method and application thereof. Background Art

[0002] Lung air leakage often occurs after thoracic surgery. In most patients, lung air leakage can heal naturally with the disappearance of residual cavity in the chest cavity and adhesion of visceral and parietal pleura, but a few patients will have persistent lung air leakage (PAL). With the aging of lung surgery patients, the incidence of emphysema and chronic obstructive pulmonary disease is increasing. The contradiction caused by persistent lung air leakage after surgery is more prominent in the practice of lung surgery. On the one hand, persistent lung air leakage leads to prolonged chest drainage time and increases the chance of intrathoracic infection. On the other hand, it affects hospitalization expenses and hospitalization time.

[0003] Experimental and clinical studies on persistent pulmonary air leak after pulmonary surgery have been conducted for decades. Many methods can be used to prevent or treat persistent pulmonary air leak, such as prolonging the indwelling time of chest drainage tubes, chemical pleurodesis, autologous hemopleurodesis, etc. Although sutures and staples are most commonly used to close wounds, achieve hemostasis, and fix implantable devices to tissues in these surgeries, they have the problems of complex use methods and poor airtightness and watertightness. Biological adhesives (including tissue adhesives, hemostats, and tissue sealants) have the potential advantages of being easy to use, airtight or watertight, and minimal tissue damage, and have been studied in depth. So far, the adhesives used in clinical practice are mainly divided into two categories according to the properties of the materials: biological adhesives (such as fibrin derivatives, chitosan, gelatin, etc.) and chemical adhesives (such as cyanoacrylates, polyethylene glycols, etc.). Recently, the U.S. Food and Drug Administration (FDA) approved fibrin-based commercial sealants (Tisseels, Evicels, Vitagelt, etc.) for lung incisions, hernia repair, treatment of refractory chylous ascites, skin grafts in burn surgery, and cleft palate repair. Most commercial sealants lack sufficient adhesive strength and durability, and are prone to induce immune responses in the body. In addition, in order to adapt to the contraction and relaxation of the lungs, the adhesive patch used to prevent lung leakage needs to have good compliance and tensile strength, but there is no biological adhesive patch designed for this problem in the prior art; further, the prior art does not consider postoperative pleural adhesion caused by adhesive materials (most of them are adhesive hydrogel single-layer structures, which can adhere to the wound to stop bleeding and prevent air leakage, but the outer layer will adhere to the tissue to cause postoperative adhesion, for example, the outer layer adheres to the pleura, resulting in postoperative pleural adhesion). Based on this, those skilled in the art are in urgent need of disclosing a patch material that can not only play a role in wet tissue adhesion but also provide physical support on the wound surface to conform to the respiratory movement of the lungs, have a certain tensile strength, and the outer layer is not easy to adhere to other biological tissues. Summary of the invention

[0004] The purpose of the present invention is to provide a double-layer asymmetric patch material for preventing air leakage after lung surgery, and its preparation method and application, so as to solve the problem that the existing clinical adhesive materials have poor bonding strength and durability and cannot adapt to the contraction and relaxation of the lungs during breathing, and the outer layer of the patch material will adhere to the tissue and cause postoperative adhesion.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery, comprising the following steps:

[0007] 1) mixing a hydrophilic polymer compound, acrylic acid, a compound having an amine coupling group, α-ketoglutaric acid, a crosslinking agent and water to obtain a hydrogel precursor solution, and performing 3D printing using the hydrogel precursor solution as 3D printing ink to obtain a 3D printed hydrogel patch;

[0008] 2) mixing the polyester with an organic solvent to obtain an electrospinning solution, and performing electrospinning to obtain a nanofiber membrane;

[0009] 3) using the hydrogel precursor solution described in step 1) as an adhesive to bond the nanofiber membrane to the 3D printed hydrogel patch to obtain a double-layer asymmetric patch material;

[0010] There is no particular order for step 1) and step 2).

[0011] Preferably, the hydrophilic polymer compound in step 1) includes one or more of polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyhydroxyethyl methacrylate, polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginic acid, alginate, oxidized sodium alginate, cellulose, oxidized cellulose, polyvinyl pyrrolidone, sodium polystyrene sulfonate, collagen and pectin.

[0012] Preferably, the compound of the amine coupling group in step 1) includes one or more of N-hydroxysuccinimide acrylate, N-hydroxysuccinimide ester, N-hydroxysulfosuccinimide ester, aldehyde, epoxide, isocyanate and catechol;

[0013] The crosslinking agent includes one or more of polyethylene glycol dimethacrylate, methacrylated gelatin, hyaluronic acid methacrylate, oxidized methacrylate alginate, N,N'-bis(acryloyl)cystamine, N,N'-methylenebis(acrylamide) and polyethylene glycol diacrylate.

[0014] Preferably, in the hydrogel precursor solution in step 1), the concentration of the hydrophilic polymer compound is 5-15wt%, the concentration of acrylic acid is 20-40wt%, the concentration of the compound with amine coupling group is 0.5-2wt%, the concentration of α-ketoglutaric acid is 0.05-1wt%, and the concentration of the crosslinking agent is 0.01-0.1wt%.

[0015] Preferably, the conditions for 3D printing in step 1) are as follows:

[0016] The ambient temperature is 25°C, the ambient humidity is 40%, the needle temperature is 20-25°C, the platform temperature is 4-10°C, the line spacing is 0.8-1.2mm, the needle specification is 0.21mm, the printing speed is 5-10mm / s, and the extrusion pressure is 0.3-0.5MPa;

[0017] Preferably, the polyester in step 2) comprises one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, polylactic acid and polyglycolic acid;

[0018] The concentration of polyester in the electrospinning solution is 10 to 30 wt %;

[0019] The organic solvent is a mixed solvent of N,N-dimethylformamide and dichloromethane, and the volume ratio of N,N-dimethylformamide to dichloromethane is 1:10 to 10:1.

[0020] Preferably, the conditions for electrospinning in step 2) are as follows:

[0021] The ambient temperature is 20°C, the ambient humidity is 25%, the voltage is 15-25 kV, the spinning extrusion speed is 0.001-0.005 mm / s, and the needle specification is 18-22 G;

[0022] The thickness of the nanofiber membrane is 20-200 μm.

[0023] The present invention also provides a double-layer asymmetric patch material prepared by the above preparation method and used for preventing air leakage after lung surgery.

[0024] The present invention also provides an application of a double-layer asymmetric patch material for preventing air leakage after lung surgery in the field of medical dressings.

[0025] The present invention has at least the following beneficial effects:

[0026] The present invention designs adhesive materials according to the characteristics of lung tissue. The 3D printed hydrogel patch prepared by 3D printing with hydrophilic polymer compounds, acrylic acid, compounds with amine coupling groups, α-ketoglutaric acid and other raw materials has good adhesion performance; and the electrospinning membrane prepared by using polyester raw materials has anti-adhesion ability. The double-layer asymmetric patch material prepared by combining the two can not only effectively adhere to the wound surface, but also avoid adhesion with other biological tissues. The double-layer asymmetric patch material also has high tensile strength and fatigue resistance, can conform to the respiratory movement of the lungs, can be used to solve the problem of air leakage after lung surgery, and can effectively avoid the occurrence of problems such as postoperative pleural adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the infrared characterization image of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1;

[0028] Figure 2 The microstructure characterization diagram of the PCL / PLGA nanofiber membrane prepared in step (2) of Example 1 at different magnifications. Figure 2 (A) is a microscopic morphology of the nanofiber membrane magnified 1000 times. Figure 2 (B) is a microscopic morphology of the nanofiber membrane magnified 7000 times;

[0029] Figure 3 This is a statistical chart of cell survival rate when the double-layer asymmetric patch prepared in Example 1 was subjected to a biocompatibility test;

[0030] Figure 4 This is a cell fluorescence photograph of the biocompatibility test of the double-layer asymmetric patch prepared in Example 1. Figure 4 (A) is a photo of cells after 72 hours of cultivation without adding the double-layer asymmetric patch material extract. Figure 4 (B) is a photo of cells after adding the extract of the double-layer asymmetric patch material and incubating for 72 hours;

[0031] Figure 5 This is a graph showing the adhesion strength test results of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1;

[0032] Figure 6 This is a graph showing the tensile strength test results of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1;

[0033] Figure 7 The hydrophilicity test results of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1 of the double-layer asymmetric patch and the PCL / PLGA nanofiber membrane prepared in step (2) of Example 1 are shown in FIG. Figure 7 (A) is a photo of the hydrophilicity test on one side of the PCL / PLGA nanofiber membrane. Figure 7 (B) is a photo of the hydrophilicity test on one side of the PVA / PAA-NHS hydrogel. Figure 7 (C) is the contact angle data diagram on both sides;

[0034] Figure 8 This is a graph showing the in vivo hemostatic performance test results of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1;

[0035] Fig. 9 This is a graph showing the tissue adhesion test results of the PVA / PAA-NHS hydrogel prepared in step (1) of Example 1;

[0036] Fig.10 This is a microstructure diagram of the double-layer asymmetric patch prepared in Example 4. DETAILED DESCRIPTION

[0037] The present invention provides a method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery, comprising the following steps:

[0038] 1) mixing a hydrophilic polymer compound, acrylic acid, a compound having an amine coupling group, α-ketoglutaric acid, a crosslinking agent and water to obtain a hydrogel precursor solution, and performing 3D printing using the hydrogel precursor solution as 3D printing ink to obtain a 3D printed hydrogel patch;

[0039] 2) mixing the polyester with an organic solvent to obtain an electrospinning solution, and performing electrospinning to obtain a nanofiber membrane;

[0040] 3) using the hydrogel precursor solution described in step 1) as an adhesive to bond the nanofiber membrane to the 3D printed hydrogel patch to obtain a double-layer asymmetric patch material;

[0041] There is no particular order for step 1) and step 2).

[0042] In the present invention, the compound having an amine coupling group refers to a compound containing a group capable of undergoing a coupling reaction with an amino group.

[0043] In the present invention, the hydrophilic polymer compound in step 1) includes one or more of polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyhydroxyethyl methacrylate, polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginic acid, alginate, oxidized sodium alginate, cellulose, oxidized cellulose, polyvinyl pyrrolidone, sodium polystyrene sulfonate, collagen and pectin;

[0044] The alginate is calcium alginate, potassium alginate or sodium alginate;

[0045] The preparation method of oxidized sodium alginate is to oxidize sodium alginate with sodium periodate at room temperature, the molar ratio of sodium periodate to sodium alginate is 5:4, and the oxidation time is 8 to 24 hours.

[0046] In the present invention, the compound of the amine coupling group in step 1) includes one or more of N-hydroxysuccinimide acrylate, N-hydroxysuccinimide ester, N-hydroxysulfosuccinimide ester (CAS 106627-54-7), aldehyde, epoxide, isocyanate and catechol;

[0047] The aldehyde is glutaraldehyde or furfural;

[0048] The epoxide is polyethylene glycol diglycidyl ether (CAS 39443-66-8) or epoxidized soybean oil (CAS 8013-07-8);

[0049] The isocyanate is hexamethylene diisocyanate (CAS 822-06-0), toluene diisocyanate (CAS 26471-62-5), isophorone diisocyanate (CAS 4098-71-9), diisocyanate polyethylene glycol (manufacturer: Meiluo Technology, catalog number 031303) or lysine diisocyanate (CAS 45172-15-4).

[0050] In the present invention, the crosslinking agent includes one or more of polyethylene glycol dimethacrylate, methacrylated gelatin, hyaluronic acid methacrylate, oxidized methacrylate alginate, N,N'-bis(acryloyl)cystamine, N,N'-methylenebis(acrylamide) and polyethylene glycol diacrylate.

[0051] In the present invention, in the hydrogel precursor solution in step 1), the concentration of the hydrophilic polymer compound is 5-15wt%, the concentration of acrylic acid is 20-40wt%, the concentration of the compound with amine coupling group is 0.5-2wt%, the concentration of α-ketoglutaric acid is 0.05-1wt%, and the concentration of the crosslinking agent is 0.01-0.1wt%. Preferably, the concentration of the hydrophilic polymer compound is 8-13wt%, the concentration of acrylic acid is 25-35wt%, the concentration of the amine coupling group is 0.5-2wt%, the concentration of α-ketoglutaric acid is 0.05-1wt%, and the concentration of the crosslinking agent is 0.01-0.1wt%. The concentration of the compound with the amine coupling group is 0.8-1.8wt%, the concentration of α-ketoglutaric acid is 0.1-0.8wt%, and the concentration of the cross-linking agent is 0.02-0.08wt%. It is more preferred that the concentration of the hydrophilic polymer compound is 10wt%, the concentration of acrylic acid is 30wt%, the concentration of the compound with the amine coupling group is 1.2-1.5wt%, the concentration of α-ketoglutaric acid is 0.2-0.5wt%, and the concentration of the cross-linking agent is 0.04-0.6wt%.

[0052] In the present invention, the conditions for 3D printing in step 1) are as follows:

[0053] The ambient temperature is 25°C, the ambient humidity is 40%, the needle temperature is 20-25°C, the platform temperature is 4-10°C, the line spacing is 0.8-1.2mm, the needle specification is 0.21mm, the printing speed is 5-10mm / s, and the extrusion pressure is 0.3-0.5MPa. Preferably, the ambient temperature is 25°C, the ambient humidity is 40%, the needle temperature is 21-24°C, the platform temperature is 5-8°C, the line spacing is 0.9-1.1mm, the needle specification is 0.21mm, the printing speed is 6-9mm / s, and the extrusion pressure is 0.35-0.45MPa. Further preferably, the ambient temperature is 25°C, the ambient humidity is 40%, the needle temperature is 22-23°C, the platform temperature is 6-7°C, the line spacing is 1mm, the needle specification is 0.21mm, the printing speed is 7-8mm / s, and the extrusion pressure is 0.4MPa.

[0054] In the present invention, the height of the 3D printed stent is 20 to 1000 μm, preferably 40 to 800 μm, more preferably 60 to 500 μm, and even more preferably 100 to 400 μm.

[0055] In the present invention, the concentration of polyester in the electrospinning solution in step 2) is 10-30wt%, preferably 14-26wt%, more preferably 18-22wt%, and more preferably 20wt%.

[0056] The organic solvent is a mixed solvent of N,N-dimethylformamide and dichloromethane, and the volume ratio of N,N-dimethylformamide to dichloromethane is 1:10 to 10:1, preferably 1:8 to 8:1, more preferably 1:5 to 5:1, and more preferably 1:3 to 3:1.

[0057] In the present invention, the conditions for electrospinning in step 2) are as follows:

[0058] The ambient temperature is 20°C, the ambient humidity is 25%, the voltage is 15-25kV, the spinning extrusion speed is 0.001-0.005mm / s, and the needle specification is 18-22G. Preferably, the ambient temperature is 20°C, the ambient humidity is 25%, the voltage is 17-23kV, the spinning extrusion speed is 0.002-0.004mm / s, and the needle specification is 19-21G. More preferably, the ambient temperature is 20°C, the ambient humidity is 25%, the voltage is 19-20kV, the spinning extrusion speed is 0.003mm / s, and the needle specification is 20G.

[0059] In the present invention, the thickness of the nanofiber membrane is 20 to 200 μm, preferably 40 to 180 μm, more preferably 60 to 150 μm, and even more preferably 80 to 120 μm.

[0060] The present invention also provides a double-layer asymmetric patch material prepared by the above preparation method and used for preventing air leakage after lung surgery.

[0061] The present invention also provides an application of a double-layer asymmetric patch material for preventing air leakage after lung surgery in the field of medical dressings.

[0062] The technical solutions provided by the present invention are described in detail in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0063] Example 1

[0064] (1) Prepare an aqueous solution with a concentration of 8 wt% of polyvinyl alcohol (PVA), 40 wt% of acrylic acid (AAc), 2 wt% of N-hydroxysuccinimide acrylate (AA-NHS), 0.2 wt% of α-ketoglutaric acid, and 0.05 wt% of polyethylene glycol dimethacrylate (PEGDMA) to obtain a 3D printing ink. The 3D printing ink is placed in a special syringe, connected to a printing needle (0.1G), and 3D printing is performed under the conditions of an ambient temperature of 25°C and a humidity of 40%. The 3D printer parameters are set as follows: needle temperature 37°C, platform temperature 10°C, printing speed 6 mm / s, extrusion speed 7 mm / s, withdrawal (SK) 0.25 mm, elevation (HP) 0.2 mm, size 10×10 mm, line spacing 1.2 mm, and bracket height 0.4 mm (the size is the length and width of the 3D printed hydrogel patch, and the bracket height is the thickness of the 3D printed hydrogel patch). After printing, it was irradiated under a 365nm ultraviolet lamp for 30 minutes for curing to obtain a polyvinyl alcohol (PVA) and PAA-NHS composite 3D printed hydrogel patch, recorded as PVA / PAA-NHS.

[0065] (2) Polylactic acid-co-glycolic acid (PLGA) and polycaprolactone (PCL) were mixed in proportion and added to a mixed solution of N,N-dimethylformamide (DMF) and dichloromethane (DCM) in a volume ratio of 3:7. The mixture was stirred magnetically (24 h) at room temperature. After the solute was completely dissolved, the solution was placed in a cleaning machine and ultrasonicated for 20 min to remove bubbles in the solution, thereby preparing an electrospinning solution (light yellow) with a PLGA concentration of 9 wt% and a PCL concentration of 9 wt%. The electrospinning solution was placed in a special syringe (20 mL), connected to a polytetrafluoroethylene hose (1 m) and a spinning needle (21 G) with an adapter, and the electrospinning equipment was used at an ambient temperature of 20°C, a humidity of 25%, a spinning voltage of 24 kV, a drum speed of 300 r / min, and a spinning extrusion speed of 0.003 mm / s. The spinning was continued for 6 h. The obtained nanofiber membrane was collected on a grounded rotating drum (diameter of 40 mm, speed of 300 r / min), wrapped in aluminum foil, and then placed under a fume hood for drying for 24 h to allow the residual solvent to fully evaporate, thereby obtaining a polycaprolactone (PCL) / polylactic acid (PLA) composite electrospinning nanofiber membrane with a thickness of 200 μm, which can be abbreviated as PCL / PLGA or PLGA / PCL.

[0066] (3) Use a special syringe (1 mL) to apply the 3D printing ink prepared in step (1) between the electrospinning membrane and the 3D printed hydrogel patch (100 μL of 3D printing ink is used per square centimeter of patch), and then use a 365 nm ultraviolet lamp to irradiate the connection for 30 minutes until the solution forms a hydrogel, and the two are bonded to obtain a double-layer asymmetric patch material.

[0067] The PVA / PAA-NHS hydrogel was characterized using a transmission Fourier transform infrared spectrometer (FTIR6700, Thermo Fisher) with a germanium attenuated total reflectance (ATR) crystal (55 degrees). The infrared spectrum is shown in Figure 1 shown.

[0068] Figure 2 The PCL / PLGA nanofiber membrane prepared in step (2) of this example is a scanning electron microscope micrograph at different magnifications (1000 times, 7000 times). Figure 2 It can be seen that the PLGA / PCL membrane obtained by electrospinning exhibits a densely connected nanofiber network structure.

[0069] Testing the biocompatibility of the double-layer asymmetric patch material:

[0070] The cell compatibility of the double-layer asymmetric patch material was evaluated by the cell viability test kit (CCK-8) experiment. The culture medium was added to the double-layer asymmetric patch material at a ratio of 10 mg: 1 mL and extracted for 24 hours to prepare the double-layer asymmetric patch material extract. After human umbilical vein endothelial cells (HUVEC) adhered to the wall and grew, the extract was added and incubated for 24 hours, 48 ​​hours, and 72 hours, and then an appropriate amount of CCK-8 solution was added to detect at 450 nm to calculate the cell survival rate, such as Figure 3 As shown, at all times (24 hours, 48 ​​hours, and 72 hours), the OD value of each experimental group increased with the extension of the incubation time, indicating that the number of cells increased significantly over time under this condition; at a fixed time point, there was no significant difference in the absorbance value between the experimental group and the control group.

[0071] The cell compatibility of the double-layer asymmetric patch material was evaluated by cell activity and cytotoxicity test kit experiments. The culture medium was added to the double-layer asymmetric patch material at a ratio of 10 mg: 1 mL and extracted for 24 hours to prepare the double-layer asymmetric patch material extract. After human umbilical vein endothelial cells (HUVEC) adhered to the wall and grew, two groups of cells were added to the double-layer asymmetric patch material extract and the culture medium without soaking the material for 72 hours, and then CalceinAM and PI dyes were added for staining for 30 minutes. The fluorescence microscope was used to observe and record the results at 488 nm and 620 nm, respectively. Figure 4 As shown, Figure 4 A in the figure is the control group, that is, the culture medium added is the culture medium that has not been extracted with the double-layer asymmetric patch material. Figure 4 B is the experimental group with the addition of the double-layer asymmetric patch material extract. Under a fluorescence microscope, the survival results of HUVECs when co-cultured with the material extract were similar to those of the control group. The experimental results show that the double-layer asymmetric patch prepared in this example is more conducive to the activity of human umbilical vein endothelial cells, has no obvious cytotoxic effect, and has good cell compatibility, which is consistent with the results of CCK-8 above.

[0072] The adhesion strength of PVA / PAA-NHS prepared in step (1) was tested:

[0073] The adhesion strength of the hydrogel PVAPAA-NHS was quantified using a universal testing machine. Using fresh pig skin as the adhesion medium, a 25 mm × 25 mm × 2 mm hydrogel was adhered between two pieces of pig skin, and the force and displacement during the movement of the fixture were recorded, such as Figure 5 As shown, the adhesion strength of the material to pig skin can reach 66kPa.

[0074] The tensile strength of the hydrogel PVA / PAA-NHS was tested:

[0075] The tensile strength of the hydrogel PVA / PAA-NHS hydrogel was quantified using a universal testing machine. The dumbbell-shaped hydrogel sample was placed on a fixture for tensile testing, such as Figure 6 The tensile strength of the hydrogel shown is 0.4 MPa.

[0076] Test the hydrophilicity of the double-layer asymmetric patch material:

[0077] The hydrophilicity of the bilayer asymmetric patch was evaluated by a static contact angle tester. Figure 7 (A) is a photo of the hydrophilicity test on one side of the PCL / PLGA nanofiber membrane. Figure 7 (B) is a photo of the hydrophilicity test on one side of the PVA / PAA-NHS hydrogel. Figure 7 (C) is the contact angle data of both sides. It can be seen from the figure that the PVA / PAA-NHS hydrogel side is hydrophilic and the PCL / PLGA nanofiber membrane side is hydrophobic. Figure 7 From (C), it can be seen that the contact angle of PCL / PLGA nanofiber membrane is 120 degrees.

[0078] The in vivo hemostatic properties of the hydrogel PVA / PAA-NHS were tested:

[0079] The liver of anesthetized mice was exposed. The liver of the mice was punctured with a 10G needle. The control group was not treated. The experimental group was adhered to the liver wound with the 3D printed hydrogel patch PVA / PAA-NHS prepared in step (1). Photos were taken at different time points to record the bleeding in the liver. Figure 8 As shown, from Figure 8 It can be seen that the amount of bleeding in the hydrogel patch group was significantly reduced compared with the control group, indicating that the 3D printed hydrogel patch PVA / PAA-NHS has in vivo hemostatic ability.

[0080] Testing the tissue adhesion properties of hydrogel PVA / PAA-NHS

[0081] The 3D printed hydrogel patch PVA / PAA-NHS prepared in step (1) was placed under the skin of mice. Fig. 9 As shown, the hydrogel can adhere to the tissue by applying pressure for a few seconds and cannot be peeled off, indicating that the hydrogel has tissue adhesion properties.

[0082] Example 2

[0083] Prepare an aqueous solution with a concentration of 5wt% polyvinyl alcohol (PVA), 50wt% acrylic acid (AAc), 1.5wt% N-hydroxysuccinimide acrylate (AA-NHS), 0.2wt% α-ketoglutaric acid, and 0.05wt% polyethylene glycol dimethacrylate (PEGDMA) to obtain a 3D printing ink. The 3D printing ink is placed in a special syringe, connected to a printing needle (0.1G), and 3D printing is performed under the conditions of an ambient temperature of 25°C and a humidity of 40%. The 3D printer parameters are set as follows: needle temperature 37°C, platform temperature 10°C, printing speed 6mm / s, extrusion speed 7mm / s, withdrawal (SK) 0.25mm, elevation (HP) 0.2mm, size 15×15mm, line spacing 1.2mm, and bracket height 0.4mm. After printing, it was irradiated under a 365nm ultraviolet lamp for 30 minutes for curing to obtain a polyvinyl alcohol (PVA) and PAA-NHS composite 3D printed hydrogel grid scaffold, recorded as PVA / PAA-NHS.

[0084] (2) Polylactic acid-co-glycolic acid (PLGA) and polycaprolactone (PCL) were mixed in proportion and added to a mixed solution of N,N-dimethylformamide (DMF) and dichloromethane (DCM) in a volume ratio of 3:7. The mixture was stirred magnetically (24 h) at room temperature. After the solute was completely dissolved, the solution was placed in a cleaning machine and ultrasonicated for 20 min to remove bubbles in the solution, thereby preparing an electrospinning solution (light yellow) with a PLGA concentration of 10 wt% and a PCL concentration of 8 wt%. The electrospinning solution was placed in a special syringe (20 mL), connected to a polytetrafluoroethylene hose (1 m) and a spinning needle (21 G) with an adapter, and the electrospinning equipment was used at an ambient temperature of 20°C, a humidity of 25%, a spinning voltage of 24 kV, a drum speed of 300 r / min, and a spinning extrusion speed of 0.003 mm / s. The spinning was continued for 6 h. The obtained nanofiber membrane was collected on a grounded rotating drum (diameter 40 mm, speed 300 r / min), wrapped in aluminum foil, and then placed under a fume hood for drying for 24 h to allow the residual solvent to fully evaporate, thereby obtaining a polycaprolactone (PCL) / polylactic acid (PLA) composite electrospinning nanofiber membrane with a thickness of 200 μm, recorded as PCL / PLGA.

[0085] (3) Use a special syringe (1 mL) to apply the 3D printing ink prepared in step (1) between the electrospinning membrane and the 3D printed hydrogel grid support (80 μL of 3D printing ink is used per square centimeter of patch), and then use a 365 nm ultraviolet lamp to irradiate the connection for 30 minutes until the solution forms a hydrogel, and bond the two together to obtain a double-layer asymmetric patch material.

[0086] Example 3

[0087] Prepare an aqueous solution with a concentration of 10wt% polyvinyl alcohol (PVA), 30wt% acrylic acid (AAc), 2wt% N-hydroxysuccinimide acrylate (AA-NHS), 0.2wt% α-ketoglutaric acid, and 0.05wt% polyethylene glycol dimethacrylate (PEGDMA) to obtain a 3D printing ink. The 3D printing ink is placed in a special syringe, connected to a printing needle (0.1G), and 3D printing is performed under the conditions of an ambient temperature of 25°C and a humidity of 40%. The 3D printer parameters are set as follows: needle temperature 37°C, platform temperature 10°C, printing speed 6mm / s, extrusion speed 7mm / s, withdrawal (SK) 0.25mm, elevation (HP) 0.2mm, size 10×10mm, line spacing 1.2mm, and bracket height 0.4mm. After printing, it was irradiated under a 365nm ultraviolet lamp for 30 minutes for curing to obtain a polyvinyl alcohol (PVA) and PAA-NHS composite 3D printed hydrogel grid scaffold, recorded as PVA / PAA-NHS.

[0088] (2) Polylactic acid-co-glycolic acid (PLGA) and polycaprolactone (PCL) were mixed in proportion and added to a mixed solution of N,N-dimethylformamide (DMF) and dichloromethane (DCM) in a volume ratio of 3:7. The mixture was stirred magnetically (24 h) at room temperature. After the solute was completely dissolved, the solution was placed in a cleaning machine and ultrasonicated for 20 min to remove bubbles in the solution, thereby preparing an electrospinning solution (light yellow) with a PLGA concentration of 8 wt% and a PCL concentration of 10 wt%. The electrospinning solution was placed in a special syringe (20 mL), connected to a polytetrafluoroethylene hose (1 m) and a spinning needle (21 G) with an adapter, and the electrospinning equipment was used at an ambient temperature of 20°C, a humidity of 25%, a spinning voltage of 24 kV, a drum speed of 300 r / min, and a spinning extrusion speed of 0.003 mm / s. The spinning was continued for 6 h. The obtained nanofiber membrane was collected on a grounded rotating drum (diameter 40 mm, speed 300 r / min), wrapped in aluminum foil, and then placed under a fume hood for drying for 24 h to allow the residual solvent to fully evaporate, thereby obtaining a polycaprolactone (PCL) / polylactic acid (PLA) composite electrospinning nanofiber membrane with a thickness of 200 μm, recorded as PCL / PLGA.

[0089] (3) Use a special syringe (1 mL) to apply the 3D printing ink prepared in step (1) between the electrospinning membrane and the 3D printed hydrogel grid support (150 μL of 3D printing ink is used per square centimeter of patch), and then use a 365 nm ultraviolet lamp to irradiate the connection for 30 minutes until the solution forms a hydrogel, and the two are bonded to obtain a double-layer asymmetric patch material.

[0090] Example 4

[0091] (1) Prepare an aqueous solution with a concentration of 8 wt% polyvinyl alcohol (PVA), 40 wt% acrylic acid (AAc), 2 wt% N-hydroxysuccinimide acrylate (AA-NHS), 0.2 wt% α-ketoglutaric acid, and 0.05 wt% polyethylene glycol dimethacrylate (PEGDMA) to obtain a 3D printing ink. The 3D printing ink is placed in a special syringe, connected to a printing needle (0.1 G), and 3D printing is performed under the conditions of an ambient temperature of 25°C and a humidity of 40%. The 3D printer parameters are set as follows: needle temperature 37°C, platform temperature 10°C, printing speed 6 mm / s, extrusion speed 7 mm / s, withdrawal (SK) 0.25 mm, elevation (HP) 0.2 mm, size 10×10 mm, line spacing 1.2 mm, and bracket height 40 μm (the size is the length and width of the 3D printed hydrogel patch, and the bracket height is the thickness of the 3D printed hydrogel patch). After printing, it was irradiated under a 365nm ultraviolet lamp for 30 minutes for curing to obtain a polyvinyl alcohol (PVA) and PAA-NHS composite 3D printed hydrogel patch, recorded as PVA / PAA-NHS.

[0092] (2) Polylactic acid-co-glycolic acid (PLGA) and polycaprolactone (PCL) were mixed in proportion and added to a mixed solution of N,N-dimethylformamide (DMF) and dichloromethane (DCM) in a volume ratio of 3:7. The mixture was stirred magnetically (24 h) at room temperature. After the solute was completely dissolved, the solution was placed in a cleaning machine and ultrasonicated for 20 min to remove bubbles in the solution, thereby preparing an electrospinning solution (light yellow) with a PLGA concentration of 9 wt% and a PCL concentration of 9 wt%. The electrospinning solution was placed in a special syringe (20 mL), connected to a polytetrafluoroethylene hose (1 m) and a spinning needle (21 G) with an adapter, and the electrospinning equipment was used to continuously spin at an ambient temperature of 20°C, a humidity of 25%, a spinning voltage of 24 kV, a drum speed of 300 r / min, and a spinning extrusion speed of 0.003 mm / s. The obtained nanofiber membrane was collected on a grounded rotating drum (diameter 40 mm, speed 300 r / min), wrapped in aluminum foil, and then placed under a fume hood for drying for 24 hours to allow the residual solvent to fully evaporate, thereby obtaining a polycaprolactone (PCL) / polylactic acid (PLA) composite electrospinning nanofiber membrane with a thickness of 30 μm, which can be abbreviated as PCL / PLGA or PLGA / PCL.

[0093] (3) Use a special syringe (1 mL) to apply the 3D printing ink prepared in step (1) between the electrospinning membrane and the 3D printed hydrogel patch (100 μL of 3D printing ink is used per square centimeter of patch), and then use a 365 nm ultraviolet lamp to irradiate the connection for 30 minutes until the solution forms a hydrogel, and the two are bonded to obtain a double-layer asymmetric patch material.

[0094] Fig.10 This is a microstructure diagram of the double-layer asymmetric patch prepared in this example, which has a double-layer asymmetric structure, with the upper layer being a PLC / PLGA layer with a thickness of 36.4 μm and the lower layer being a PVA / PAA-NHS layer with a thickness of 46.7 μm.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery, characterized in that: The following steps are involved: 1) mixing a hydrophilic polymer compound, acrylic acid, a compound having an amine coupling group, α-ketoglutaric acid, a crosslinking agent and water to obtain a hydrogel precursor solution, and performing 3D printing using the hydrogel precursor solution as 3D printing ink to obtain a 3D printed hydrogel patch; 2) mixing the polyester with an organic solvent to obtain an electrospinning solution, and performing electrospinning to obtain a nanofiber membrane; 3) using the hydrogel precursor solution described in step 1) as an adhesive to bond the nanofiber membrane to the 3D printed hydrogel patch to obtain a double-layer asymmetric patch material; There is no particular order for step 1) and step 2).

2. A method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 1, characterized in that: The hydrophilic polymer compound in step 1) includes one or more of polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyhydroxyethyl methacrylate, polyethylene glycol, polyurethane, casein, albumin, gelatin, chitosan, hyaluronic acid, alginic acid, alginate, oxidized sodium alginate, cellulose, oxidized cellulose, polyvinyl pyrrolidone, sodium polystyrene sulfonate, collagen and pectin.

3. The method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 2, characterized in that: The compound of the amine coupling group in step 1) includes one or more of N-hydroxysuccinimide acrylate, N-hydroxysuccinimide ester, N-hydroxysulfosuccinimide ester, aldehyde, epoxide, isocyanate and catechol; The crosslinking agent includes one or more of polyethylene glycol dimethacrylate, methacrylated gelatin, hyaluronic acid methacrylate, oxidized methacrylate alginate, N,N'-bis(acryloyl)cystamine, N,N'-methylenebis(acrylamide) and polyethylene glycol diacrylate.

4. A method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 2 or 3, characterized in that: In the hydrogel precursor solution in step 1), the concentration of the hydrophilic polymer compound is 5-15wt%, the concentration of acrylic acid is 20-40wt%, the concentration of the compound with amine coupling group is 0.5-2wt%, the concentration of α-ketoglutaric acid is 0.05-1wt%, and the concentration of the crosslinking agent is 0.01-0.1wt%.

5. The method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 4, characterized in that: The conditions for 3D printing in step 1) are as follows: The ambient temperature is 25°C, the ambient humidity is 40%, the needle temperature is 20-25°C, the platform temperature is 4-10°C, the line spacing is 0.8-1.2mm, the needle specification is 0.21mm, the printing speed is 5-10mm / s, and the extrusion pressure is 0.3-0.5Mpa.

6. The method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 5, characterized in that: The polyester in step 2) comprises one or more of polylactic acid-glycolic acid copolymer, polycaprolactone, polylactic acid and polyglycolic acid; The concentration of polyester in the electrospinning solution is 10 to 30 wt %; The organic solvent is a mixed solvent of N,N-dimethylformamide and dichloromethane, and the volume ratio of N,N-dimethylformamide to dichloromethane is 1:10 to 10:

1.

7. The method for preparing a double-layer asymmetric patch material for preventing air leakage after lung surgery according to claim 6, characterized in that: The conditions for electrospinning in step 2) are as follows: The ambient temperature is 20°C, the ambient humidity is 25%, the voltage is 15-25 kV, the spinning extrusion speed is 0.001-0.005 mm / s, and the needle specification is 18-22 G; The thickness of the nanofiber membrane is 20-200 μm.

8. The double-layer asymmetric patch material for preventing air leakage after lung surgery prepared by the preparation method of the double-layer asymmetric patch material for preventing air leakage after lung surgery as claimed in any one of claims 1 to 7.

9. Use of the double-layer asymmetric patch material for preventing air leakage after lung surgery as claimed in claim 8 in the field of medical dressings.

Citation Information

Patent Citations

  • Multi-layered antiadhesion barrier

    CN101257935A

  • Anti-adhesion membrane adopting double-layer structure and preparation method of anti-adhesion membrane

    CN105194739A

  • Double-layer asymmetric dressing for promoting skin wound repair and preparation method thereof

    CN114028603A

  • Janus hydrogel dressing for postoperative adhesion prevention and preparation method thereof

    CN117414464A

  • Multifunctional composite pleura repairing patch and preparation method thereof

    CN117695448A